Analisis Faktor-Faktor yang Berpengaruh terhadap Produksi dan Pendapatan Usahatani Rumput Laut di Kawasan Minapolitan (Studi Kasus di Kecamatan Tinanggea, Kabupaten Konawe Selatan, Provinsi Sulawesi Tenggara) - Sadimantara, Fahria Nadiryati; Rianse, Ilma Sarimustaqiyma (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2017)
This research was aimed to analyze the factors affecting seaweed production and farming income in a minapolitan area. The study was conducted from March 2013 to May 2013 in Tinanggea District, South Konawe District, South East Of Sulawesi with 30 respondents of seaweed farmers. Regression analysis Cobb-Douglas concluded that the variables that significantly affect the production of seaweed are the land area, number of seeds, and the number of labor. While the results of the Cobb-Douglas benefit analysis concluded that the variables that significantly affect farm income are seaweed farmer seed prices, equipment prices, labor costs, experience, and land area.